2021
DOI: 10.1039/d1ra02582a
|View full text |Cite
|
Sign up to set email alerts
|

A highly selective “turn-on” water-soluble fluorescent sensor for gallium ion detection

Abstract: In this work, a highly selective water-soluble “turn-on” fluorescent sensor for gallium ion recognition was reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 56 publications
0
8
0
Order By: Relevance
“…This limit is the third lowest among the thiophene-based fluorescent Ga 3+ chemosensors (Table S1). [27,29,30,33] For studying binding properties, we produced a Job's plot experiment (Figure S4). The result demonstrated that DHTC and Ga 3+ created 1:1 stoichiometry, which was confirmed using ESI-MS (Figure S5).…”
Section: Spectroscopic Test Of Dhtc With Ga 3+mentioning
confidence: 99%
See 1 more Smart Citation
“…This limit is the third lowest among the thiophene-based fluorescent Ga 3+ chemosensors (Table S1). [27,29,30,33] For studying binding properties, we produced a Job's plot experiment (Figure S4). The result demonstrated that DHTC and Ga 3+ created 1:1 stoichiometry, which was confirmed using ESI-MS (Figure S5).…”
Section: Spectroscopic Test Of Dhtc With Ga 3+mentioning
confidence: 99%
“…They adopt several moieties for instance, rhodamine, sulfonamide, quinolone, benzothiazole, and a naphthyl group. [5,6,[23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] However, some of them are restricted by the use of complex synthetic methods of preparation. Thiophene derivatives with good optical properties could be used as a functional group for chemosensors.…”
mentioning
confidence: 99%
“…Among N-acylhydrazones, 2-furoic and 2-thiophenecarboxylic acid-based N-acylhydrazones have gained considerable interest as colorimetric and fluorescence sensors owing to their impressive spectroscopic features and the added advantage of furan and thiophene as πlinkers. [15,19,21,22,[50][51][52][53][54][55][56][57][58] Their synthetic methods include reacting aromatic aldehydes with 2-furoic hydrazide or 2-thiophenecarboxylic acid hydrazide in solvents that need extended reaction durations (3-48 hours). Therefore, we present herein a fast and efficient method for the synthesis of N-acylhydrazones via a solid-state melt reaction of aromatic aldehydes with 2-furoic hydrazide or 2-thiophenecarboxylic acid hydrazide under catalyst-and solvent-free conditions that, to the best of our knowledge, has never been discovered (Scheme 1d).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the scope of substrates for this method has not been thoroughly examined. Among N ‐acylhydrazones, 2‐furoic and 2‐thiophenecarboxylic acid‐based N ‐acylhydrazones have gained considerable interest as colorimetric and fluorescence sensors owing to their impressive spectroscopic features and the added advantage of furan and thiophene as π‐linkers [15,19,21,22,50–58] . Their synthetic methods include reacting aromatic aldehydes with 2‐furoic hydrazide or 2‐thiophenecarboxylic acid hydrazide in solvents that need extended reaction durations (3–48 hours).…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge the detection of NH 4 + and HPO 4 2À ions using a Schiff base fluorescence sensor is rarely reported. Based on our previous work,[40][41][42][43] in this paper, three novel Zn(II) Schiff base complexes were synthesized by solvent evaporation at room temperature using 4-substituted salicylic aldehyde derivatives NaHL (NaHL = sodium (S,E)-2-((4-chloro-2-hydroxybenzylidene) amino) propanoate) and zinc acetate. The coordination mode of [Zn(L) (H 2 O)] n (1) and [Zn(L) (H 2 O)] n (2) was basically the same, and [Zn 2 (L) 2 (bipy)] (3) was constructed as a quad-nuclear structural unit due to the introduction of the second ligand 4,4 0 -dipyridine connection.…”
mentioning
confidence: 99%